Introduction to the Special Issue on Safe food for infants: the importance of pursuing integrated approaches to monitor and reduce the risks of biological, chemical, and physical hazards in infant food during the key developmental years - Massimo Pettoello-Mantovani; Julije Mestrovic; Angel Carrasco-Sanz; Hilary Hoey; Tudor Lucian Pop; Eli Somekh; Mehmet Vural; Aida Mujkic; Ida Giardino; Leyla Namazova-Baranova (Global Pediatrics, 2022)
Owing to increasing populations and global threats, the integrity and safety of global food chains are at risk. In many countries, simply getting enough to eat can be an issue, with poor quality food often contaminated with hazardous agents, whereas in developed countries the pressure to deliver cheap, affordable food may affect quality and safety. The purpose of this Special issue on Safe food for infants is to emphasize the importance of pursuing integrated approaches to monitor and reduce the risks of biological, chemical, and physical hazards in infant food. A careful integrated approach is proposed to be instrumental in order to minimize the hazards to infant health during the key developmental years and protect children from penalizing nutritional disorders and gastrointestinal diseases.